Improving City Plan Certificate Services Electorally (e KRK) Based on Digital City Spatial Planning - Dwi Putranto Riau (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As one of the requirements for the management of Building Approval (PBG), the City Plan Description (KRK) must be fulfilled by article 19 PP 16 of 2021 concerning Building Buildings. So far, the City Plan That contains the designation and intensity of the building is based on the Detailed Plan of Urban Spatial Planning (RDTRK) or the Building and Environmental Planning Plan (RTBL). The public is still many who do not know about the City Spatial Plan because it has not been socialized by RDTRK and RTBL and is still limited through the Regency / City Government website. Spatial Planning products have not been digitally packaged through the WEB and Android applications. The purpose of this research is to analyze the readiness of organizational capacity and resources (HR, infrastructure, e-KRK and budget) in preparing e-KRK based on the Digital Spatial Plan and cultural readiness of the community in information technology for e-KRK licensing. This research uses the Qualitative Descriptive method. Primary data collection through in-depth interviews with staff who handle SKRK in districts/cities that have implemented KRK and secondary data through websites, media mas, journals, and others. Data analysis by performing data reduction steps, presentation, and conclusion or verification. The results of this study are expected to increase KRK service performance with the provision of electronic KRK (e-KRK) based on RDTRK and RTBL digital by Government Regulation 16 of 2021 concerning Building Buildings and Government Regulation 21 of 2021 on Spatial Planning. Resources (HR, infrastructure e KRK, organizational culture and budget) are available, and the culture of people who have received information technology permits.